Active power loss allocation among generators and loads in an interconnected integrated energy system - Sultana R.; Ravi Kumar D.; Raju G.S. (My University, 2025)
In deregulation, often issues and challenges arise. The issue of power loss allocation is a common and an important one among them. The generators must compensate transmission loss by generating more power. In competitive electricity market environment, no suppliers would want to generate more to compensate this loss as it will increase their production costs. In general both generators and consumers are required to pay for the losses because they both use the network and thus are responsible for the losses occurred. If there is no specified method to handle this problem, maximum percentage of transmission losses is allocated to generator and less percentage of transmission losses to consumers. With this the fuel cost for the generation will increase which is unfair. The main intention of this paper is for fair loss allocation method to share losses only among generators by sharing losses in the each transmission line between corresponding buses and also methods to share losses between generators and consumers thus making both players cover up for the cost of losses in the competitive market. © International Sciences Press, India.